Sinus histiocytosis with massive lymphadenopathy and subglottic stenosis: A case report - Chalermchai Chintrakarn (2018)
An 18 year-old woman presented with massive cervical lymphadenopathy. She also had bilateral parotid gland enlargement, and later upper airway obstruction from subglottic mass compression. Surgical excision of lymph nodes and bilateral total parotidectomy with facial nerve preservation were selected. Direct laryngoscopy and CO2 laser excision were used to remove the subglottic mass. Airway was secured by tracheostomy and after that it was removed. Histologic finding was Sinus histiocytosis with massive lymphadenopathy (SHML) that involved the subglottic. SHML is very rare, probably less than 1000 cases reported in the literature and this is the 6th case in the literature that involved the subglottic. There are no standard treatment modalities. The treatment is comprised of surgery, steroid, chemotherapy and local control. In the present case the authors chose surgery, steroid and local control of disease in the subglottic by using CO2 laser excision. Now, the disease is under control.